US Gambling Stagnation: Will New Gambling Forms Make a Difference? - Lambert, Thomas E. (Critical Gambling Studies, 2023)
Much has been written recently in the popular press about the rise of sports gambling, historical horse racing or instant racing (HHR), and esports. However, despite this, some note an overall decline in the popularity of gambling and gaming in general as horse racing (pari-mutuel) wagering has declined dramatically over the decades and as casino and lottery revenues have fallen slightly since before the Great Recession. This exploratory research note examines the trends in US gambling over the last several decades and explores whether the new forms of gambling will stem and reverse overall gambling stagnation in the United States. Despite reports of new gambling outlet successes, it appears that sports gambling, HHR, and esports have not done much to stop the overall fall in gambling revenues. This is probably due to stagnant disposable personal income growth.